Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper analyses Paraguay's effective interest spreads using various methodologies. Interest rate spreads in Paraguay continue to be some of the highest in Latin America. A series of bank crises in the late 1990s and early 2000s weakened the financial system and pushed up spreads. The analysis suggests that operational costs, rising profits, and the need to cover credit and liquidity risks are the main factors behind Paraguay's effective spreads. Improving data quality and mechanisms for sharing credit information could contribute to reduced spreads. Although the empirical results suggested that banking concentration has not given rise to greater spreads, adding new banking entrants may lower margins by increasing competition within the sector.